2014
DOI: 10.1007/s40092-014-0081-7
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization in WEDM of D3 tool steel using integrated approach of Taguchi method & Grey relational analysis

Abstract: In this paper, wire electrical discharge machining of D3 tool steel is studied. Influence of pulse-on time, pulse-off time, peak current and wire speed are investigated for MRR, dimensional deviation, gap current and machining time, during intricate machining of D3 tool steel. Taguchi method is used for single characteristics optimization and to optimize all four process parameters simultaneously, Grey relational analysis (GRA) is employed along with Taguchi method. Through GRA, grey relational grade is used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 16 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…The F-ratio value indicates the significance of process parameters. Larger the value of F-ratio represent most significance process parameter [11][12]. Here, Welding current is most significant process parameter followed by weld time and electrode force.…”
Section: Anova For Grey Relational Gradementioning
confidence: 98%
See 1 more Smart Citation
“…The F-ratio value indicates the significance of process parameters. Larger the value of F-ratio represent most significance process parameter [11][12]. Here, Welding current is most significant process parameter followed by weld time and electrode force.…”
Section: Anova For Grey Relational Gradementioning
confidence: 98%
“…The optimal Grey relational grade ηopt is predicted as follows [10][11][12]. The results of confirmation experiment obtained by grey relation analysis are as shown in Table 6.…”
Section: Prediction Of Grg Under Optimum Parametersmentioning
confidence: 99%
“…Taguchi-based Grey relational analysis, to find the optimal process parameter setting for multi-matrix composite using molybdenum wire of 0.18 mm diameter, as electrode is applied by Lal et al (2015). Similar technique for optimisation was used by Shivade and Shinde (2014) for D3 tool steel material. Nayak and Mahapatra (2016) applied an artificial neural network (ANN) model to determine the relationship between input parameters and performance characteristics for taper cutting of deep cryo-treated Inconel 718 with cryo-treated coated Bronco cut-W.…”
Section: Introductionmentioning
confidence: 99%
“…Bobbili [1] reported that Pon, Poff and servo voltage were the significant factors for Ra and MRR for cutting armor tool steel. Shivade and Shinde [17] evaluated the cutting performance of WEDM for D3 tool steel. The results showed that MRR increases with the increase in Pon and peak current and decreases with the increase in Poff .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an optimization technique has become an essential tool in finding the exact com-bination of process parameters. Many researchers used various optimization techniques in order to optimize the process parameters of WEDM [6,17,21]. In addition to these, Kumar [8] used taguchi method while investigating the effects of cutting parameters on material removal rate for EN-42 using WEDM process.…”
Section: Introductionmentioning
confidence: 99%